Advanced applications of the nanohybrid membrane of chitosan/nickel oxide for photocatalytic, electro-biosensor, energy storage, and supercapacitors. (June 2022) - El-Shafai, Nagi M.; Shukry, Mustafa; Sharshir, Swellam W.; Ramadan, Mohamed S.; Alhadhrami, A.; El-Mehasseb, Ibrahim
Abstract: The present work explains the importance of electron transfer between nickel oxide nanoparticles (NiO NPs) and nano chitosan (Cs NPs) surface for various applications, where nanohybrid membrane (NHM) of (Cs@NiO) is combined and characterized successfully. The photocatalytic activity against the organic pollutants via the strong creation of the reactive oxygen species (ROS), where the efficiency with rhodamine B (RhB) was 26.7%, 37%, and 80% for NiO NPs, Cs@NiO NHM, and Cs@NiO (in KCl), respectively. While methylene blue (MB) was 29%, 77%, and 86% for NiO NPs, Cs@NiO NHM, and Cs@NiO (KCl), respectively. Also, the improved electrochemical properties of NHM enable to work of a modified electrode for the supercapacitors, energy storage, and biosensor applications for glucose in the blood. The water desalination was performed in Kafrelsheikh city between 8 am to 6 pm, July 2021, where the desalination productivity increases by approximately 46.7% percent. The cytotoxicity of NHM has been revealed with histopathological examination and biochemical analysis for thirty male Wistar rats. The lower dose of Cs@NiO NHM showed significant improvement in all obtained biochemical and histopathological studies that returned to the Cs NPs that act as antioxidants. The results prove that NHM is a unique membrane for various applications due to its electronic and surface properties. Graphical abstract: Unlabelled Image Highlights: Upgrading the optical and electrochemical properties of nickel oxide nanoparticle Novel membrane for water desalination, super capacitance and energy storage Chitosan/nickel membrane electro biosensor for glucose in the blood Chitosan/nickel membrane acts as a powerful antioxidant membrane.